Verbal Positional Memory in 7‐Month‐Olds. Issue 1 (30th August 2014) - Benavides‐Varela, Silvia; Mehler, Jacques
<x xml:space="preserve">Abstract</x> Verbal memory is a fundamental prerequisite for language learning. This study investigated 7‐month‐olds' (N = 62) ability to remember the identity and order of elements in a multisyllabic word. The results indicate that infants detect changes in the order of edge syllables, or the identity of the middle syllables, but fail to encode the order of middle syllables. This suggests that the representational format of multisyllabic words is determined by core mnemonic biases, which favor accurate encoding of edges and limits the encoding of temporal order for internal segments. The studies support accounts proposing that content and order are encoded separately; in addition, the data show that this dissociation occurs early in development.